An Exploration and Practice on the Ideological and Political Education of International Politics Course - Wang, Baisong (IJRDO- Journal of Educational Research, 2019)
The ideological and political education of the course is a kind of new idea and new mode in China’s universities. Its aim is to explore the resources of ideological and political education for different subjects and specialized courses and make it in the same direction with ideological and political courses. Therefore, as a carrier of course education, we should dig into its moral elements, explore its unique educational value, and further improve teaching design and innovating approaches to achieve the mission of strengthening morality in the process of course education.